Fabrication of fluorinated graphene based aramid nanofibers films with excellent thermal conductivity and mechanical properties - Minh-Canh Vu; Minh-Sang Tran; Quang Bang Tao; Van-Thanh Hoang (Tạp chí Khoa học và Công nghệ, 2023)
The rapid advancement of technology has spurred the development of a wide range of sophisticated electronic devices leading to an increasing demand for the utilization of thermoconductive materials to address thermal management. However, most of the available thermoconductive materials possess inadequate mechanical properties and low resistance to temperatures. To address this limitation, this study focuses on fabricating the thermoconductive films using aramid nanofiber (ANF) as strengthening components and fluorinated graphene (FG) as a thermoconductive filler. The films are prepared through the simple vacuum filtration method. The obtained FG/ANF film with 40 wt% of FG reached the in-plane thermal conductivity of 9 W/mK. Additionally, the FG40/ANF film exhibits excellent mechanical properties, including a tensile strength exceeding 110 MPa and toughness greater than 7.2 MJ/m³. Given these remarkable characteristics, the FG/ANF film holds significant promise as a material for dissipating heat in electronic devices, particularly in applications that demand high mechanical performance and temperature stability.